phân tích thành nhân tử : x^4 + 2x^2 y + y^2 -9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: 2x+4=2(x+2)
b: \(x^2+2xy+y^2-9=\left(x+y-3\right)\left(x+y+3\right)\)
Sửa đề : \(9\left(x+y-1\right)^2-4\left(2x+3y+1\right)^2\)
\(=\left(9x+9y-9\right)^2-\left(8x+12y+4\right)^2\)
\(=\left(9x+9y-9-8x-12y-4\right)\left(9x+9y-9+8x+12y+4\right)\)
\(=\left(x-3y-13\right)\left(17x+21y-5\right)\)
Đúng là Tú có khác (:
9( x + y - 1 )2 - 4( 2x + 3y + 1 )2
= 32( x + y - 1 )2 - 22( 2x + 3y + 1 )2
= [ 3( x + y - 3 ) ]2 - [ 2( 2x + 3y + 1 ) ]2
= ( 3x + 3y - 3 )2 - ( 4x + 6y + 2 )2
= [ ( 3x + 3y - 3 ) - ( 4x + 6y + 2 ) ][ ( 3x + 3y - 3 ) + ( 4x + 6y + 2 ) ]
= ( 3x + 3y - 3 - 4x - 6y - 2 )( 3x + 3y - 3 + 4x + 6y + 2 )
= ( -x - 3y - 5 )( 7x + 9y - 1 )
\(1,=x\left(x^2-2x+1-y^2\right)=x\left[\left(x-1\right)^2-y^2\right]=x\left(x-y-1\right)\left(x+y-1\right)\\ 2,=\left(x+y\right)^3\\ 3,=\left(2y-z\right)\left(4x+7y\right)\\ 4,=\left(x+2\right)^2\\ 5,Sửa:x\left(x-2\right)-x+2=0\\ \Leftrightarrow\left(x-2\right)\left(x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\)
\(x^4-y^2\left(2x-y\right)^2\)
\(=x^4-\left(2xy-y^2\right)^2\)
\(=\left(x^2-2xy+y^2\right)\left(x^2+2xy-y^2\right)\)
\(=\left(x-y\right)^2\left(x^2+2xy-y^2\right)\)
\(=\left(3x-3y\right)^2-\left(2x+2y\right)^2=\left(3x-3y-2x-2y\right)\left(3x-3y+2x+2y\right)\)
\(=\left(x-5y\right)\left(5x-y\right)\)
Bài 4:
\(x^3-2x^2+x=x\left(x-1\right)^2\)
\(5\left(x-y\right)-y\left(x-y\right)=\left(x-y\right)\left(5-y\right)\)
\(x^2-12x+36=\left(x-6\right)^2\)
`9(x-y)^2-4(x+y)^2`
`=[3(x-y)]^2-[2(x+y)]^2`
`=(3x-3y)^2-(2x+2y)^2`
`=(3x-3y+2x+2y)(3x-3y-2x-2y)`
`=(5x-y)(x-5y)`
\(9\left(x-y\right)^2-4\left(x+y\right)^2\\ =\left[3\left(x-y\right)\right]^2-\left[2\left(x+y\right)\right]^2\\ =\left[3\left(x-y\right)-2\left(x+y\right)\right]\left[3\left(x-y\right)+2\left(x+y\right)\right]\\ =\left(3x-3y-2x-2y\right)\left(3x-3y+2x+2y\right)\\ =\left(x-5y\right)\left(5x-y\right)\)
Bài làm:
Ta có: \(9\left(x-y\right)^2-4\left(x+y\right)^2=\left[3\left(x-y\right)\right]^2-\left[2\left(x+y\right)\right]^2\)
\(=\left(3x-3y-2x-2y\right)\left(3x-3y+2x+2y\right)=\left(x-5y\right)\left(5x-y\right)\)
Học tốt!!!!
Ta có :
\(9\left(x-y\right)^2-4\left(x+y\right)^2=9x^2-18xy+9y^2-4x^2-8xy-4y^2\)
\(=5x^2-26xy+5y^2==\left(5x-y\right)\left(x-5y\right)\)
\(x^4+2x^2y+y^2-9\)
\(=\left(x^2+y\right)^2-3^2\)
\(=\left(x^2+y-3\right)\left(x^2+y+3\right)\)
\(x^4+2x^2y+y^2-9\)
\(=\left(x^2\right)^2+2.x^2.y+y^2-3^2\)
\(=\left(x^2+y\right)^2-3^2\)
\(=\left(x^2+y-3\right)\left(x^2+y+3\right)\)